Voltammetric Behaviour and Analysis of Fluchloralin. Issue 4 (2010) - Balaji, K.; Sridevi, C.; Ananda Kumar Reddy, N.; Reddy, K. Mohana Muni Sidda; Suresh Reddy, C.
Abstract : The electrochemical reduction behavior of fluchloralin has been studied by D.C.polarography, differential pulse polarography, millicoulometry and controlled potential electrolysis in the universal buffers ranging from 2.0 to 12.0. Kinetic parameters were evaluated and a reduction mechanism was proposed. A simple and rapid differential pulse polarographic method has been developed for the determination of fluchloralin in formulations, grains, soils and spiked water samples. The lower detection limit was found to be 1.5×10 -8 M. Both the standard addition and calibration methods were used for the analytical measurements.